Anti-dendrite lithium metal negative electrode, preparation method thereof and solid-state battery
By setting a control layer composed of boron nitride nanotubes and solid electrolyte materials on the surface of the lithium metal negative electrode, the problems of dendrites growth and side reactions during the large-scale charge and discharge of the lithium metal negative electrode are solved, and the cycle performance and safety performance of the battery are improved.
Patent Information
- Application Number
- CN202510246048.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-04
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-03-04
AI Technical Summary
The lithium metal negative electrode is prone to growth of lithium dendrites during the battery charge and discharge process, resulting in short circuits, and high activity leads to side reactions in contact with the electrolyte, forming a SEI film and gradually thickening, affecting battery performance.
The control layer is arranged on the surface of the lithium metal negative electrode. The control layer is composed of boron nitride nanotubes and solid electrolyte materials to form a stable three-dimensional network structure, providing high mechanical strength, thermal conductivity and lithium ion storage channels, and inhibit dendrites' growth and lithium metal expansion.
The cycling and safety performance of lithium metal batteries is significantly improved, dendrites are inhibited and the thickness of SEI film is suppressed, and the interfacial impedance and thermal runaway risk are reduced.
Smart Images

Figure CN119786531A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium metal batteries, and in particular to an anti-dendritic lithium metal negative electrode and a preparation method thereof and a solid-state battery. Background Art
[0002] In recent years, with the depletion of fossil energy and the increasingly serious environmental pollution problems, the new energy industry has received more and more attention. Compared with common electrochemical secondary batteries such as lead-acid batteries and nickel-hydrogen batteries, lithium-ion batteries have the advantages of high energy density, long cycle life, and no memory effect. As a new type of lithium battery, lithium metal batteries have higher specific energy density and theoretical specific capacity, and are expected to be used in the next generation of high energy density power batteries. However, due to the high chemical activity and low melting point of lithium metal, lithium metal also faces many challenges when used as a negative electrode of the battery: 1. When charging and discharging lithium metal with a large current, dendrites will inevitably be generated due to uneven deposition of lithium ions. The gradual growth of lithium dendrites will pierce the diaphragm and cause a short circuit; 2. During the battery charge and discharge cycle, a series of side reactions will occur between the electrolyte and the lithium metal negative electrode to generate SEI film, consuming lithium ions. As the reaction proceeds, the SEI film gradually thickens, increasing the interface resistance and reducing the coulomb efficiency of the battery; 3. The lithium metal negative electrode will generate a lot of heat during the charge and discharge process, especially when charging and discharging at high rates, the heat generation increases sharply, which can easily cause thermal runaway and lead to battery damage. Therefore, the development of lithium metal battery negative electrode materials with good safety performance, low production cost, excellent electrical properties and strong anti-dendrite performance has become one of the research hotspots.
[0003] CN119050486A discloses a method for constructing a SEI layer of a lithium metal battery and a lithium metal battery, wherein the preparation method comprises dissolving KI, InCl3 and crown ether in water to prepare a crown ether KInI4 filler; adding the filler to a PEO-based solid electrolyte to prepare a lithium metal battery; and constructing a LiF-LiI-LiInO2 co-grown SEI layer through the charge and discharge cycle of the lithium metal battery. The method can significantly reduce the crystallinity of PEO by introducing the LiF-LiI-LiInO2 co-grown SEI layer, significantly improve the ionic conductivity, increase the migration rate of lithium ions, reduce the interface impedance, and improve the cycle performance of the battery. However, the method cannot regulate the thickness of the artificial SEI layer, and its application is limited to polymer solid electrolytes, which has little effect on improving the safety performance of the battery. Therefore, research on lithium metal batteries needs to be considered from many aspects to improve the interface strength, safety performance and cycle performance of the battery. Summary of the invention
[0004] The present invention aims to solve the following technical problems: lithium metal negative electrode materials are prone to grow lithium dendrites during high-rate charge and discharge of batteries, and lithium dendrites will pierce solid electrolytes or diaphragms to cause short circuits between the positive and negative electrodes of the battery. In addition, due to the high activity of lithium metal, a series of side reactions will occur when it comes into contact with electrolytes or solid-state battery electrolytes, releasing a large amount of heat, and at the same time, a SEI film will be generated to inhibit side reactions and protect the negative electrode. As the reaction proceeds, the SEI film gradually thickens and ruptures, consuming a large amount of lithium ions. Therefore, it is necessary to set a control layer on the surface of the lithium metal negative electrode. The control layer has high mechanical strength, inhibits the growth of lithium dendrites and the expansion of lithium metal, has a three-dimensional structure that can store and regulate lithium ion deposition and deintercalation, has high thermal conductivity, prevents thermal runaway of the battery, improves the affinity of lithium metal with various electrolytes, and ensures the consistency of the multilayer structure of the bipolar solid-state battery.
[0005] The inventors found that boron nitride nanotubes (BNNTs) can form various nanostructures, and their properties do not change with size and chirality. Their electronic properties are similar to those of hexagonal boron nitride, with a large band gap of about 6 eV, which conducts lithium ions but not electrons, and has electrical insulation. At the same time, boron nitride nanotubes have high mechanical strength, with a theoretical modulus of 1.1 TPa. As a control layer, they have extremely high mechanical strength and can inhibit the growth of lithium dendrites. Their thermal stability can promote the conduction process of lithium ions, reduce interfacial impedance, and facilitate reaction heat diffusion. Combining boron nitride nanotubes with solid electrolytes can build a stable three-dimensional network structure as a control layer. The network structure regulates the deposition of lithium ions, builds a storage layer for lithium ions, and reduces the stress concentration caused by lithium ion accumulation. Solid electrolytes can improve lithium ion mobility, increase ion conductivity, form stable lithium ion pathways, and improve the cycle and rate performance of lithium metal negative electrodes in many aspects.
[0006] Specifically, the present invention provides an anti-dendritic lithium metal negative electrode, which includes an active material layer and a control layer arranged on the active material layer and in contact with the active material layer, wherein the active material layer is a lithium metal and / or lithium alloy layer; the control layer is a layer of a three-dimensional network structure comprising boron nitride nanotubes and a solid electrolyte material, and the boron nitride nanotubes and the solid electrolyte material are uniformly mixed in the control layer; the boron nitride nanotubes have a diameter of 10-500nm, a length of 1-100μm, and a Young's modulus ≥0.5TPa; the solid electrolyte material includes a polymer matrix, an inorganic reinforcing material, a lithium salt, a thickener and a hydrophilic additive; the mass ratio of the polymer matrix, the inorganic reinforcing material, the lithium salt, the thickener and the hydrophilic additive is (1-10): (1-5): (1-5): (1-5): (1-5); the mass ratio of the boron nitride nanotubes and the solid electrolyte is (0.5-5): 1.
[0007] Optionally, the control layer has a thickness of 1-100 μm and an elastic modulus of ≥6 GPa.
[0008] Optionally, the boron nitride nanotubes of the control layer include single-walled boron nitride nanotubes, multi-walled boron nitride nanotubes, nanoribbon boron nitride nanotubes, or a combination of at least two of them.
[0009] The solid electrolyte material in the control layer includes a polymer matrix, an inorganic reinforcing material, a lithium salt, a thickener and a hydrophilic additive;
[0010] Optionally, the polymer matrix includes one or more copolymers or mixtures of polystyrene butadiene copolymer, polyethylene oxide, polyvinylidene fluoride, epoxy resin, polyurethane, polyacrylonitrile, polyimide, polycarbonate, polyvinylidene fluoride, polytetrafluoroethylene, copolymer of polyvinylidene fluoride and hexafluoropropylene, polyacrylate, polyaniline, polyether sulfone, cellulose acetate, polylactic acid, polycaprolactone, polytrimethylene carbonate, polyethylene terephthalate and polylactic glycolic acid;
[0011] Optionally, the inorganic reinforcing material includes one or more of alumina, silica, magnesium oxide, titanium dioxide, graphene, carbon nanotubes, or a mixture of a mixture of several thereof.
[0012] Optionally, the lithium salt includes one or more combinations of lithium hexafluorophosphate, lithium trifluoromethanesulfonate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium perchlorate, lithium bis(fluorosulfonyl imide), lithium bis(trifluoromethanesulfonyl imide), lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium carbonate, lithium oxalate, lithium bicarbonate, lithium acetate, lithium halide, lithium sulfate, and lithium hydroxide.
[0013] Combining boron nitride nanotubes with solid-state electrolytes can construct a stable three-dimensional network-like fiber structure, which provides a large number of active sites for the transmission of lithium ions, assists lithium ion migration, promotes the dissociation of lithium salts, and improves ionic conductivity and battery cycle performance.
[0014] Optionally, the thickener includes one or more of carboxymethyl cellulose, sesbania gum, sodium starch phosphate, triethyl phosphate, and sodium polyacrylate.
[0015] Optionally, the hydrophilic additive includes a combination of one or more of polyethylene glycol, polyvinyl alcohol, polyoxyethylene ether, carboxylates, sulfonates, sulfates, phosphates, imidazole ionic liquids, pyridine ionic liquids, quaternary ammonium ionic liquids, quaternary phosphonium ionic liquids, pyrrolidine ionic liquids, and piperidine ionic liquids.
[0016] Adding thickeners and hydrophilic additives can increase the uniformity and hydrophilicity of the slurry, prevent the control layer slurry from settling, reduce the hydrophilic angle, increase the wettability of the slurry with the lithium metal strip or the carrier layer, and facilitate process operation.
[0017] Optionally, the mass ratio of the polymer substrate, the inorganic reinforcing material, the lithium salt, the thickener and the hydrophilic additive is (5-10):(2-3):(2-3):(2-3):(1-3).
[0018] Optionally, the mass ratio of the boron nitride nanotubes to the solid electrolyte is (0.5-2):1.
[0019] Optionally, the active material layer includes a metal lithium layer, a lithium alloy layer, or a combination of the two; preferably, the lithium alloy layer includes an alloy of lithium and one or more of silicon, indium, silver, carbon, magnesium, aluminum, boron, tin, gallium, cobalt, gold, barium, bismuth, calcium, germanium, mercury, platinum, zinc, lead, antimony, cadmium, and cobalt.
[0020] Optionally, the thickness of the active material layer is 3 μm-300 μm, preferably 10 μm-100 μm.
[0021] Optionally, the thickness ratio of the control layer to the active material layer is (0.001-1):1, preferably (0.01-0.1):1.
[0022] Optionally, the lithium metal negative electrode also includes a current collector, and the current collector includes at least one of copper foil, aluminum foil, stainless steel foil, nickel foil, tin foil, carbon nanotube paper, carbon fiber paper, copper mesh, aluminum mesh, stainless steel mesh, nickel foam, and an organic fiber film with a metal plated surface.
[0023] Another aspect of the present invention provides a method for preparing the anti-dendritic lithium metal anode as described above, the method comprising:
[0024] (1) Plasma cleaning and drying of boron nitride nanotubes and solid electrolyte materials;
[0025] (2) Weigh corresponding proportions of boron nitride nanotubes, polymer matrix and inorganic reinforcement material, mix them, refine the powder particles and mix them evenly;
[0026] (3) Weighing a certain amount of solvent, adding lithium salt, thickener and hydrophilic additive according to corresponding mass fractions, mixing and stirring, and then adding the mixture of boron nitride nanotubes, polymer matrix and inorganic reinforcing material obtained in step (2), mixing and stirring to obtain a uniform and viscous slurry;
[0027] (4) The slurry obtained in step (3) is disposed on the surface of the active material layer to form a uniform coating, and then dried to obtain the anti-dendrite lithium metal negative electrode.
[0028] Optionally, the gas used for plasma cleaning in step (1) includes one or a combination of two of hydrogen, oxygen, nitrogen, argon, helium, etc.
[0029] Optionally, the plasma cleaning time in step (1) is 3-5 minutes.
[0030] Plasma acting on powders can effectively change the physical and chemical properties of powders, increase the hydrophilicity of the powder surface, thereby improving the wettability of the powder particle surface, enhancing the interfacial compatibility of powder particles in the medium, and making the particles easily dispersed in water or organic compounds.
[0031] Optionally, the drying and dehumidification temperature in step (1) is 60-100° C., and the drying time is 1-5 h.
[0032] Optionally, the method for mixing the boron nitride nanotubes, the polymer matrix and the inorganic reinforcing material in step (2) comprises ball milling, chemical precipitation, sol-gel method, ultrasonic mixing method, preferably ball milling.
[0033] Optionally, the ball milling speed of the ball milling method is 100-600 rpm, and the ball milling time is 3-6 h.
[0034] Optionally, the solvent described in step (3) includes any one of N-methylpyrrolidone, tetrahydrofuran, dimethyl ether, dichloromethane, ethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, diethylene glycol monomethyl ether, tetraethylene glycol dimethyl ether, dimethyl sulfate, polyether ketone, or a combination of at least two thereof.
[0035] Optionally, the mass ratio of the lithium salt, thickener, hydrophilic additive and solvent described in step (3) is (1-5): (1-5): (1-5): (85-97). If the mass ratio of the lithium salt to the solvent is too small, the ion conductivity of the lithium salt cannot be exerted; if the mass ratio of the lithium salt to the solvent is too large, the lithium salt concentration is too high, which affects the electrolyte infiltration; if the mass ratio of the thickener to the solvent is too small, a stable and uniform three-dimensional network structure cannot be formed; if the mass ratio of the thickener to the solvent is too large, the powder is easy to agglomerate; if the mass ratio of the hydrophilic additive to the solvent is too small, the effect of improving the hydrophilicity of the slurry is small; if the mass ratio of the hydrophilic additive to the solvent is too large, the cycle performance of the battery is affected. Preferably, it is (2-3): (2-3): (1-3): (91-95).
[0036] Optionally, the mass ratio of the boron nitride nanotubes, polymer matrix, inorganic reinforcing material and solvent in step (3) is (0.5-2): (0.1-2): (0.1-1): (95-99.3), preferably (0.5-1.5): (0.1-1): (0.1-0.5): (97-99.3). If the mass ratio of the boron nitride nanotubes to the solvent is too small, the slurry concentration is low, and the three-dimensional network structure of the boron nitride nanotubes is sparse, and its excellent mechanical strength and lithium storage performance cannot be exerted; if the mass ratio of the boron nitride nanotubes to the solvent is too large, the slurry concentration is high, the control layer has high mechanical strength and does not fit the metal lithium negative electrode, the fibers are intertwined, the interface impedance is increased, and the battery cycle performance is affected; if the mass ratio of the polymer base material, the inorganic reinforcing material and the solvent is too small, the stability of the three-dimensional network structure is low; if the mass ratio of the polymer matrix, the inorganic reinforcing material and the solvent is too large, the solid content of the slurry increases, it is not easy to coat evenly, and it is easy to agglomerate.
[0037] Optionally, in step (3), the lithium salt, thickener and hydrophilic additive are added and mixed with stirring at a speed of more than 1100 rpm, and the stirring time is 1-20 hours.
[0038] Optionally, in step (3), boron nitride nanotubes are added, and the polymer matrix and the inorganic reinforcing material are mixed and stirred at a speed of more than 1200 rpm for a stirring time of 1-20 hours.
[0039] Optionally, the method of disposing the slurry of step (3) on the active material layer in step (4) includes any one of coating, film transfer, spraying, spin coating, roller pressing, and infiltration, or a combination of at least two thereof.
[0040] Optionally, the coating is disposed on the active material layer by a film transfer method, wherein the slurry is evenly coated on the surface of the release film, transferred to the surface of the active material layer, and vacuum dried at 50° C.-60° C. for 8-12 hours.
[0041] Another aspect of the present invention provides a solid-state battery, which includes a positive electrode, a negative electrode and a solid electrolyte disposed between the positive electrode and the negative electrode; wherein the negative electrode is the anti-dendritic metal lithium negative electrode as described above.
[0042] Optionally, the active material of the positive electrode is any one of layered oxides, polyanion active materials, lithium-rich oxides or spinel oxides, or a combination of at least two thereof.
[0043] Optionally, the solid-state battery includes a lithium-sulfur solid-state battery, a bipolar solid-state battery, a sulfide solid-state battery, a polymer solid-state battery, a halide solid-state battery, an oxide solid-state battery, and an organic-inorganic composite solid-state battery.
[0044] Optionally, the solid-state battery is a bipolar solid-state battery, which is composed of n (n=2-20) layers stacked in a structure of "current collector-positive electrode-solid electrolyte-negative electrode-current collector-positive electrode-solid electrolyte-negative electrode".
[0045] The present invention has at least one of the following beneficial technical effects:
[0046] (1) A control layer is set on the surface of the metal lithium negative electrode. The boron nitride nanotubes in the control layer are mixed with the solid electrolyte to form a stable three-dimensional network structure, which can provide extremely high mechanical strength for the negative electrode interface of the lithium metal battery. In addition, a lithium ion storage channel is set up to regulate the uniform deposition of lithium ions, inhibit the generation and growth of dendrites, and alleviate the expansion of lithium metal, thereby improving the cycle performance of the metal lithium battery.
[0047] (2) A control layer is set on the surface of the metallic lithium negative electrode. The boron nitride nanotubes in the control layer have thermal stability and thermal conductivity, which ensure the safety performance during the battery cycle. They have multiple active sites, regulate the conduction rate of lithium ions, provide multiple diffusion paths for lithium ions, and reduce the reaction overpotential.
[0048] (3) A control layer is set on the surface of the metallic lithium negative electrode. The control layer acts as an artificial SEI protective layer for the lithium metal negative electrode, isolating lithium from direct contact with the solid electrolyte, making metallic lithium compatible with a variety of solid electrolytes, reducing the occurrence of side reactions, and can be applied to a variety of solid-state batteries.
[0049] (4) The anti-dendritic lithium metal negative electrode interface is stable, which is particularly suitable for application in solid-state batteries, especially bipolar solid-state batteries. The multilayer structure of bipolar solid-state batteries ensures cycle stability.
[0050] (5) The preparation method of anti-dendritic lithium metal anode is simple, easy and efficient. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] Figure 1 A schematic diagram of lithium ion deposition of the anti-dendrite lithium metal negative electrode of the present invention applied to a solid-state battery;
[0052] Figure 2 A schematic diagram of the structure of the anti-dendrite lithium metal negative electrode of the present invention applied to a bipolar solid-state battery;
[0053] Figure 3 This is a SEM image of the boron nitride nanotube fiber structure in the control layer prepared in Example 1;
[0054] Figure 4 The morphology image and Young's modulus test image of the control layer prepared in Example 1 under an atomic force microscope;
[0055] Figure 5Cyclic test curves of the anti-dendrite negative electrode at a charge and discharge current of 0.3C in Examples 1, 2, 3 and Comparative Example 1;
[0056] Among them, 1-current collector, 2-positive electrode, 3-solid electrolyte, 4-control layer, 5-active material layer. DETAILED DESCRIPTION
[0057] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0058] The anti-dendrite lithium metal negative electrode provided by the present invention is illustrated by way of example. Figure 1 The anti-dendritic lithium metal negative electrode comprises a control layer 4 and an active material layer 5.
[0059] Figure 2 The overall structure is a schematic diagram of a bipolar solid-state battery, including n layers of repeated structural unit structures (2≤n≤20), each structural unit including a current collector 1, a positive electrode 2, a solid electrolyte 3, a control layer 4 and an active material layer 5.
[0060] Example 1
[0061] This embodiment provides an anti-dendrite lithium metal negative electrode, wherein the negative electrode structure is stacked in the order of a current collector, an active material layer, and a control layer;
[0062] The control layer includes boron nitride nanotubes with a diameter of 200nm, a length of 5μm, and an elastic modulus of 0.6TPa, polyethylene oxide (PEO), aluminum oxide (Al2O3), lithium hexafluorophosphate (LiPF6), carboxymethyl cellulose (CMC), a hydrophilic additive polyethylene glycol (PEG), and a solvent of N-methylpyrrolidone (NMP), wherein the mass ratio of boron nitride nanotubes, PEO, Al2O3, LiPF6, CMC, PEG, and NMP is 8:5:2:2:1:1:81. The thickness of the control layer is 5μm, the Young's modulus is 8GPa, the active material layer is a 50μm lithium metal layer, and the current collector is a copper foil.
[0063] The method for preparing the anti-dendritic lithium metal negative electrode comprises the following steps:
[0064] (1) BNTs, PEO and Al2O3 were cleaned with nitrogen plasma for 3 min and dried in a vacuum drying oven at 80 °C for 3 h;
[0065] (2) Weigh 8g of boron nitride nanotubes, 5g of PEO, and 2g of Al2O3 materials and put them into a ball mill at 500rpm for 3h to refine the powder particles and mix them evenly;
[0066] (3) Weigh 81 g NMP, add 2 g LiPF6, 1 g CMC, and 1 g PEG, stir at 1100 rpm for 12 h, then add the powder mixed in step (2), stir at 1200 rpm for 12 h to obtain a uniform and viscous slurry;
[0067] (4) The slurry of step (3) is transferred to the surface of the active material layer to form a uniform coating, and then dried under vacuum at 50° C. for 8 h, and then cooled to room temperature to obtain the anti-dendritic lithium metal negative electrode. The prepared negative electrode is assembled into an all-solid-state battery.
[0068] Example 2
[0069] This embodiment provides an anti-dendrite lithium metal negative electrode, wherein the negative electrode structure is stacked in the order of a current collector, an active material layer, and a control layer;
[0070] The control layer includes boron nitride nanotubes with a diameter of 300nm, a length of 10μm, and an elastic modulus of 0.8TPa, polystyrene butadiene copolymer (SBR), silicon dioxide (SiO2), lithium bis(fluorosulfonyl)imide (LiFSI), carboxymethyl cellulose (CMC), a hydrophilic additive sodium dodecylbenzene sulfonate (SDBS), and a solvent of ethylene glycol dimethyl ether (DME), wherein the mass ratio of boron nitride nanotubes, SBR, SiO2, LiFSI, CMC, SDBS, and DME is 9:5:3:2:1:80. The thickness of the control layer is 5μm, the Young's modulus is 10GPa, the active material layer is a 50μm lithium metal layer, and the current collector is copper foil.
[0071] The method for preparing the anti-dendritic lithium metal negative electrode comprises the following steps:
[0072] (1) The boron nitride nanotubes, SBR and SiO2 were cleaned with nitrogen plasma for 3 min and dried in a vacuum drying oven at 80 °C for 3 h;
[0073] (2) Weigh 9 g of boron nitride nanotubes, 5 g of SBR, and 3 g of SiO2 material and put them into a ball mill at 300 rpm for 3 h to refine the powder particles and mix them evenly;
[0074] (3) Weigh 80 g of DME, add 3 g of LiFSI, 2 g of CMC, and 1 g of SDBS, stir at 1100 rpm for 12 h, then add the powder mixed evenly in step (2), stir at 1200 rpm for 12 h to obtain a uniform and viscous slurry;
[0075] (4) The slurry of step (3) is transferred to the surface of the active material layer to form a uniform coating, and then dried under vacuum at 50° C. for 8 h, and then cooled to room temperature to obtain the anti-dendritic lithium metal negative electrode. The prepared negative electrode is assembled into an all-solid-state battery.
[0076] Example 3
[0077] This embodiment provides an anti-dendrite lithium metal negative electrode, wherein the negative electrode structure is stacked in the order of a current collector, an active material layer, and a control layer;
[0078] The control layer includes boron nitride nanotubes with a diameter of 500nm, a length of 20μm, and an elastic modulus of 1TPa, polyvinylidene fluoride (PVDF), magnesium oxide (MgO), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), triethyl phosphate (TEP), a hydrophilic additive 1-methylimidazole chloride, and a solvent of dimethyl carbonate, wherein the mass ratio of boron nitride nanotubes, PVDF, MgO, LiTFSI, TEP, 1-methylimidazole chloride, and dimethyl carbonate is 9:5:3:2:1:80. The control layer has a thickness of 5μm, a Young's modulus of 12GPa, the active material layer is a 50μm lithium metal layer, and the current collector is a copper foil.
[0079] The method for preparing the anti-dendritic lithium metal negative electrode comprises the following steps:
[0080] (1) The boron nitride nanotubes, PVDF and MgO were cleaned with nitrogen plasma for 3 min and dried in a vacuum drying oven at 80 °C for 3 h;
[0081] (2) Weigh 9 g of boron nitride nanotubes, 5 g of PVDF, and 3 g of MgO materials and put them into a ball mill at 500 rpm for 3 h to refine the powder particles and mix them evenly;
[0082] (3) Weigh 80 g of dimethyl carbonate, add 3 g of LiTFSI, 2 g of TEP, and 1 g of 1-methylimidazole chloride, stir at 1100 rpm for 12 h, then add the powder mixed in step (2), stir at 1200 rpm for 12 h to obtain a uniform and viscous slurry;
[0083] The slurry in step (3) is transferred onto the surface of the active material layer to form a uniform coating, and then dried at 50°C in a vacuum oven for 8 hours, and then cooled to room temperature to obtain the anti-dendritic lithium metal negative electrode. The prepared negative electrode is assembled into an all-solid-state battery.
[0084] Example 4
[0085] Compared with Example 1, the only difference is that the mass ratio of boron nitride nanotubes to the slurry is replaced with 30%, and the other conditions remain unchanged.
[0086] Example 5
[0087] Compared with Example 1, the only difference is that the mass ratio of boron nitride nanotubes to the slurry is replaced with 6%, and the other conditions remain unchanged.
[0088] Example 6
[0089] Compared with Example 1, the only difference is that the mass ratio of PEO in the slurry is replaced by 10%, and the other conditions remain unchanged.
[0090] Example 7
[0091] Compared with Example 1, the only difference is that the mass ratio of PEO in the slurry is replaced by 2%, and the other conditions remain unchanged.
[0092] Example 8
[0093] Compared with Example 1, the only difference is that the mass ratio of Al2O3 in the slurry is replaced by 5%, and the other conditions remain unchanged.
[0094] Example 9
[0095] Compared with Example 1, the only difference is that the mass ratio of Al2O3 in the slurry is replaced with 1%, and the other conditions remain unchanged.
[0096] Example 10
[0097] Compared with Example 1, the only difference is that the mass ratio of LiPF6 in the slurry is replaced by 5%, and the other conditions remain unchanged.
[0098] Embodiment 11
[0099] Compared with Example 1, the only difference is that the mass ratio of LiPF6 in the slurry is replaced with 1%, and the other conditions remain unchanged.
[0100] Example 12
[0101] Compared with Example 1, the only difference is that the mass ratio of CMC to the slurry is replaced by 3%, and the other conditions remain unchanged.
[0102] Embodiment 13
[0103] Compared with Example 1, the only difference is that the mass ratio of CMC to the slurry is replaced by 0.5%, and the other conditions remain unchanged.
[0104] Example 12
[0105] Compared with Example 1, the only difference is that the mass ratio of PEG to the slurry is replaced by 3%, and the other conditions remain unchanged.
[0106] Embodiment 13
[0107] Compared with Example 1, the only difference is that the mass ratio of PEG to the slurry is replaced by 0.5%, and the other conditions remain unchanged.
[0108] Embodiment 14
[0109] Compared with Example 1, the only difference is that the thickness of the control layer is replaced with 1 μm, and the other conditions remain unchanged.
[0110] Embodiment 15
[0111] Compared with Example 1, the only difference is that the thickness of the control layer is replaced with 50 μm, and the other conditions remain unchanged.
[0112] Example 16
[0113] Compared with Example 1, the only difference is that the thickness of the active material layer is replaced with 5 μm, and the other conditions remain unchanged.
[0114] Embodiment 17
[0115] Compared with Example 1, the only difference is that the thickness of the active material layer is replaced with 100 μm, and the other conditions remain unchanged.
[0116] Embodiment 18
[0117] Compared with Example 1, the only difference is that the lithium metal strip of the active material layer is replaced by a lithium-magnesium alloy strip, and the other conditions remain unchanged.
[0118] Embodiment 19
[0119] Compared with Example 1, the only difference is that 8g of boron nitride nanotubes, 5g of PEO, and 2g of Al2O3 materials are weighed and mixed using an ultrasonic mixing method, and the other conditions remain unchanged.
[0120] Embodiment 20
[0121] Compared with Example 1, the only difference is that the control layer is disposed on the active material layer by coating, and a 50 μm coating blade is used on the coater to evenly coat the control layer slurry on the active material layer at a speed of 25 m / min, and other conditions remain unchanged.
[0122] Embodiment 21
[0123] Compared with Example 1, the only difference is that the prepared anti-dendrite negative electrode is used to assemble a bipolar battery.
[0124] Comparative Example 1
[0125] This comparative example provides an all-solid-state battery, which directly uses a 50 μm lithium metal strip as the negative electrode.
[0126] Comparative Example 2
[0127] This comparative example provides an all-solid-state battery, which directly uses a 50 μm lithium-magnesium alloy strip as the negative electrode.
[0128] Comparative Example 3
[0129] This comparative example provides an all-solid-state battery. Compared with Example 1, boron nitride nanotubes are not added to the anti-dendrite negative electrode structure, and the other conditions are the same as those of Example 1.
[0130] Comparative Example 4
[0131] This comparative example provides an all-solid-state battery. Compared with Example 1, no solid electrolyte material is added to its anti-dendrite negative electrode structure, and other conditions are the same as those of Example 1.
[0132] Comparative Example 5
[0133] This comparative example provides an all-solid-state battery. Compared with Example 1, no polymer matrix is added to the anti-dendritic negative electrode structure solid electrolyte material, and the other conditions are the same as those of Example 1.
[0134] Comparative Example 6
[0135] This comparative example provides an all-solid-state battery. Compared with Example 1, no inorganic reinforcing material is added to the anti-dendritic negative electrode structure solid electrolyte material, and the other conditions are the same as those of Example 1.
[0136] Comparative Example 7
[0137] This comparative example provides an all-solid-state battery. Compared with Example 1, no thickener is added to the anti-dendritic negative electrode structure solid electrolyte material, and the other conditions are the same as those of Example 1.
[0138] Comparative Example 8
[0139] This comparative example provides an all-solid-state battery. Compared with Example 1, no hydrophilic additive is added to the anti-dendritic negative electrode structure solid electrolyte material, and the other conditions are the same as those of Example 1.
[0140] Comparative Example 9
[0141] This comparative example provides an all-solid-state battery. Compared with Example 1, the anti-dendritic negative electrode structure boron nitride nanotubes and solid electrolyte materials are not plasma cleaned, and the other conditions are the same as those in Example 1.
[0142] Comparative Example 10
[0143] This comparative example provides an all-solid-state battery. Compared with Example 1, its anti-dendrite negative electrode structure control layer is replaced by a transferred PEO coating, and the other conditions are the same as those of Example 1.
[0144] Comparative Example 11
[0145] This comparative example provides an all-solid-state battery. Compared with Example 1, its anti-dendrite negative electrode structure control layer is replaced by a transferred Al2O3 coating, and the other conditions are the same as those in Example 1.
[0146] Comparative Example 12
[0147] This comparative example provides an all-solid-state battery. Compared with Example 1, its anti-dendrite negative electrode structure control layer is replaced by a transferred carbon fiber coating, and the other conditions are the same as those of Example 1.
[0148] Comparative Example 13
[0149] This comparative example provides an all-solid-state battery. Compared with Example 1, the boron nitride nanotubes in its anti-dendrite negative electrode structure control layer are replaced with boron nitride particles with a particle size of 200 nm, and the other conditions are the same as those in Example 1.
[0150] Comparative Example 14
[0151] This comparative example provides a bipolar solid-state battery, whose anti-dendrite negative electrode configuration is the same as that of comparative example 1.
[0152] Preparation of all-solid-state batteries:
[0153] The battery produced is a mold battery with an electrode active area of 0.8 cm 2 .
[0154] The preparation method of the solid electrolyte is as follows: 100 mg of lithium phosphorus sulfur chloride sulfide (LSPCl) electrolyte is taken and pressed into a Teflon tablet pressing mold at a pressure of 300 MPa to prepare an electrolyte layer;
[0155] The preparation method of the positive electrode is as follows: 20 mg LiNi 0.8 Co 0.1 Mn 0.1 O2, small-particle LSPCl electrolyte, and carbon black are uniformly mixed in a mass ratio of 75:25:2, and pressed into a Teflon tablet pressing mold at a pressure of 300 MPa to obtain a positive electrode sheet of the battery;
[0156] The preparation method of the all-solid-state battery is as follows: the prepared positive electrode sheet is pressed on one side of the LSPCl electrolyte at a pressure of 300MPa, and then the functional lithium metal negative electrode is pressed on the other side of the electrolyte layer at 20MPa to prepare the all-solid-state battery.
[0157] The preparation method of the bipolar solid-state battery is as follows: the prepared positive electrode sheet is pressed on one side of the solid electrolyte layer at a pressure of 300MPa, and the functional lithium metal negative electrode is pressed on the other side of the electrolyte layer to obtain a layer of repeating structural units. The current collector is placed between multiple repeating structural units, the repeating structural units are stacked, and an external pressure of 20MPa is applied to assemble into a bipolar solid-state battery.
[0158] Solid-state battery negative electrode performance test:
[0159] The negative electrodes provided in Examples 1-20 and Comparative Examples 1-12 were respectively assembled into solid-state batteries for cycle performance testing. The specific testing method was as follows: at 25°C, constant current charging and constant current discharging were adopted, the charge and discharge voltage range was 2.7-4.3V, the charge and discharge rate was 0.3C or 2C, the initial capacity of the battery was recorded as C0, and the battery completed a full charge and discharge, which was recorded as a cycle; charging and discharging were performed according to the above method, and the capacity of the battery after each cycle was tested until the capacity of the battery was 80% of C0 or the battery was short-circuited or the charge and discharge efficiency was lower than 98%, and the number of cycles at this time was recorded.
[0160] The negative electrodes provided in Example 21 and Comparative Example 13 were respectively assembled into bipolar solid-state batteries for cycle performance testing. The specific testing method was as follows: at 25°C, constant current charging and constant current discharging were adopted, the charge and discharge voltage range was 5.0-8.5V, the charge and discharge rate was 0.3C or 2C, the initial capacity of the battery was recorded as C1, and the battery completed a full charge and discharge, which was recorded as one cycle; charging and discharging were performed according to the above method, and the capacity of the battery after each cycle was tested until the capacity of the battery was 80% of C1 or the battery short-circuited or the charge and discharge efficiency was lower than 98%, and the number of cycles at this time was recorded.
[0161] Young's modulus test:
[0162] The control layer is set on the lithium metal negative electrode, and the Young's modulus test is performed on the negative electrode interface. Using an atomic force microscope, a micro-cantilever that is extremely sensitive to weak forces is fixed at one end, and a tiny needle tip is at the other end. The needle tip gently contacts the interface, and the repulsive force between the needle tip and the interface is controlled to be constant during scanning. The micro-cantilever with the needle tip will fluctuate perpendicular to the interface direction corresponding to the equipotential surface of the force between the needle tip and the interface atoms. Using optical detection or tunnel current detection, the position change of the micro-cantilever corresponding to each scanning point can be measured, so that the sample morphology can be obtained and the Young's modulus can be calculated.
[0163] The cycle performance test results of the all-solid-state battery assembled with the functional lithium metal negative electrodes prepared in Examples 1-21 and Comparative Examples 1-14 are shown in Table 1.
[0164] Table 1 Battery cycle performance test results
[0165]
[0166]
[0167] Battery cycle performance test analysis results:
[0168] (1) Comparison between Examples 1-3 and Comparative Example 1
[0169] Examples 1-3 show that adding the control layer of the present invention to the surface of the lithium metal negative electrode improves the cycle performance of the all-solid-state battery. The control layer is composed of boron nitride nanotubes + solid electrolyte. Since the boron nitride material conducts ions, lithium ions are deposited between the bottom of the control layer and the active material layer. Figure 3 The figure shows a 3000-fold magnified SEM image of boron nitride nanotubes. It can be seen from the figure that the boron nitride nanotubes present a fibrous structure, with multiple fibers interwoven together to form a network structure that is relatively loose. Boron nitride nanotubes are combined with solid electrolytes to form a stable network structure that can act as a lithium ion storage layer to alleviate the expansion of lithium metal. The types and combinations of polymer matrices, inorganic reinforcing materials, thickeners, hydrophilic additives, and solvents in the solid electrolyte materials of Examples 1-3 are different. Compared with the use of pure lithium metal strip as the negative electrode in Comparative Example 1, the lithium metal negative electrode with an additional control layer significantly improves the battery's cycle performance at 0.3C and 2C charge and discharge rates. According to Table 1 and Figure 5 According to the data, at a charge and discharge rate of 0.3C, the pure lithium belt can only be cycled 60 times, and the anti-dendritic lithium metal negative electrode can be cycled 224 times; at a charge and discharge rate of 2C, the pure lithium belt can be cycled 30 times, and the anti-dendritic lithium metal negative electrode can be cycled 156 times. Figure 4 This is the morphology of the control layer under an atomic force microscope. The Young's modulus of the control layer is calculated to be 7.772 GPa, which shows that the control layer has an extremely high Young's modulus, which is higher than the Young's modulus of 4 GPa of the original SEI layer of pure lithium metal. It can effectively inhibit the generation and growth of lithium dendrites and improve the cycle performance of the battery.
[0170] (2) Comparison between Example 1 and Examples 4-17
[0171] Examples 4-17 show the effects of changes in the content of boron nitride nanotubes in the control layer and the content of each component material of the solid electrolyte on the cycle life of the all-solid-state battery. From the data in Table 1, it can be seen that when the content of boron nitride nanotubes is too high, the mechanical strength of the control layer increases, but the fit with the lithium negative electrode is not tight, the fiber nanotubes are staggered, and the interface impedance increases; when the content of boron nitride nanotubes is low, the three-dimensional network structure is loose, and the storage of lithium ions is small, all of which will affect the cycle performance of the battery. If the content of each component material of the solid electrolyte is too high or too low, it will affect the stability of the three-dimensional network structure and the mobility of lithium ions, thereby reducing the cycle performance of the battery. In addition, the thickness of the control layer and the thickness of the active material layer should also be precisely controlled. If the thickness of the control layer is too thick, the interface impedance of the lithium metal battery will increase; if the thickness of the control layer is too thin, the protection effect on the lithium negative electrode interface is weak. This shows that the content of each material in the control layer of the present invention and the thickness of the control layer and the active material layer should be adjusted and determined to ensure excellent results.
[0172] (3) Comparison between Example 1 and Examples 19-20
[0173] Examples 19-20 show the effects of different processes on the performance of all-solid-state batteries. Example 19 uses different powder mixing methods to mix solid powders evenly, which has little effect on the battery cycle performance. Example 20 replaces the transfer method with a coating method. As long as the uniformity of the control layer coating on the active material layer is guaranteed and the surface tension of the lithium metal strip during the drying process is controlled, the battery cycle performance will have little effect.
[0174] (4) Comparison between Example 18 and Comparative Example 2
[0175] Example 18 and Comparative Example 2 show the effect of setting a control layer on the lithium alloy layer on the cycle performance of the all-solid-state battery. Compared with pure metal lithium, the lithium alloy layer is doped with one or more metal elements to improve the cycle performance of metal lithium. From the data in Table 1, after setting the control layer on the alloy layer, the cycle performance of the lithium metal battery is greatly improved. At a charge and discharge rate of 0.3C, the cycle is improved by 149 cycles, and at a charge and discharge rate of 2C, the cycle is improved by 116 cycles.
[0176] (5) Comparison between Example 1 and Comparative Examples 3-9
[0177] Comparative Examples 3-9 show the importance of the control layer composition materials provided by the present invention, and the influence of different materials on the cycle performance of all-solid-state batteries. From the data in Table 1, the cycle of the battery is reduced when different control layer materials are missing, and when only boron nitride nanotubes or solid electrolyte materials are present, the cycle performance of the battery is less improved compared with pure lithium ribbons.
[0178] (6) Comparison between Example 1 and Comparative Examples 10-12
[0179] Comparative Examples 10-12 show the effect of replacing the control layer material with polymer material, inorganic reinforcing material and carbon nanofiber on the performance of all-solid-state batteries. The control layer material provided by the present invention can inhibit the growth of lithium dendrites, alleviate the expansion of lithium metal, improve lithium ion conduction, improve the mechanical strength of the interface, and set up lithium ion storage space. However, after replacing the control layer material, the cycle performance of the lithium metal battery is improved less.
[0180] (7) Comparison between Example 1 and Comparative Example 13
[0181] Example 1 and Comparative Example 13 show the effect of replacing the boron nitride nanotubes in the control layer with boron nitride nanoparticles on the cycle performance of the all-solid-state battery. From the data in Table 1, the improvement of the battery cycle performance by boron nitride nanoparticles is small. The main reason is that boron nitride nanoparticles are usually two-dimensional sheets or zero-dimensional particles, without the three-dimensional network structure of boron nitride nanotubes. The protective layer prepared by boron nitride nanoparticles has a loose structure, poor uniformity, low mechanical strength, weak ability to inhibit lithium dendrites, and weak effect on improving the uniformity of lithium ion distribution, so the improvement of battery cycle performance is limited.
[0182] (8) Comparison between Example 21 and Comparative Example 14
[0183] Example 21 and Comparative Example 14 show that the control layer provided by the present invention is applied to a bipolar battery to improve the cycle performance of the bipolar battery. As can be seen from Table 1, at a charge and discharge rate of 0.3C, the battery cycle is improved by 117 cycles, and at a charge and discharge rate of 2C, the battery cycle is improved by 96 cycles. The control layer reduces the side reactions that occur when lithium metal directly contacts the solid electrolyte, while improving the consistency of the multi-layer interface, inhibiting dendrite growth and regulating the deposition of lithium ions, and the cycle improvement effect is obvious.
[0184] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can make appropriate changes and modifications to the above embodiments. Therefore, the present invention is not limited to the specific embodiments disclosed and described above, and some modifications and changes to the present invention should also fall within the scope of protection of the claims of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.
Claims
1. An anti-dendritic lithium metal negative electrode, characterized in that The negative electrode includes an active material layer and a control layer disposed on and in contact with the active material layer; Wherein, the active material layer is a lithium metal and / or lithium alloy layer; The control layer is a layer of a three-dimensional network structure including boron nitride nanotubes and solid electrolyte materials, and the boron nitride nanotubes and the solid electrolyte materials are uniformly mixed in the control layer; The boron nitride nanotube has a diameter of 10-500 nm, a length of 1-100 μm, and an elastic modulus of ≥0.5 TPa; The solid electrolyte material comprises a polymer matrix, an inorganic reinforcing material, a lithium salt, a thickener and a hydrophilic additive; The mass ratio of the polymer matrix, the inorganic reinforcing material, the lithium salt, the thickener and the hydrophilic additive is (1-10): (1-5): (1-5): (1-5): (1-5); The mass ratio of the boron nitride nanotubes to the solid electrolyte material is (0.5-5):
1.
2. The anti-dendritic lithium metal negative electrode according to claim 1, characterized in that The boron nitride nanotubes of the control layer include single-walled boron nitride nanotubes, multi-walled boron nitride nanotubes, and nanoribbon boron nitride, or a combination of at least two thereof; The control layer has a thickness of 1-100 μm and a Young's modulus of ≥6 GPa.
3. The anti-dendritic lithium metal negative electrode according to claim 1 or 2, characterized in that The polymer matrix includes one or more copolymers or mixtures of polystyrene butadiene copolymer, polyethylene oxide, polyvinylidene fluoride, epoxy resin, polyurethane, polyacrylonitrile, polyimide, polycarbonate, polyvinylidene fluoride, polytetrafluoroethylene, copolymer of polyvinylidene fluoride and hexafluoropropylene, polyacrylate, polyaniline, polyether sulfone, cellulose acetate, polylactic acid, polycaprolactone, polytrimethylene carbonate, polyethylene terephthalate and polylactic glycolic acid; The inorganic reinforcing material includes one or more of alumina, silicon dioxide, magnesium oxide, titanium dioxide, graphene, carbon nanotubes, or a mixture of a mixture of alumina, silicon dioxide, magnesium oxide, titanium dioxide, graphene, and carbon nanotubes; The lithium salt includes one or more combinations of lithium hexafluorophosphate, lithium trifluoromethanesulfonate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium perchlorate, lithium bis(fluorosulfonyl imide), lithium bis(trifluoromethanesulfonyl imide), lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium carbonate, lithium oxalate, lithium bicarbonate, lithium acetate, lithium halide, lithium sulfate, and lithium hydroxide; The thickener includes one or more of carboxymethyl cellulose, sesbania gum, sodium starch phosphate, triethyl phosphate, and sodium polyacrylate; The hydrophilic additive includes one or more combinations of polyethylene glycol, polyvinyl alcohol, polyoxyethylene ether, carboxylates, sulfonates, sulfate esters, phosphate esters, imidazole ionic liquids, pyridine ionic liquids, quaternary ammonium ionic liquids, quaternary phosphonium ionic liquids, pyrrolidine ionic liquids, and piperidine ionic liquids.
4. The anti-dendritic lithium metal negative electrode according to claim 1, characterized in that The active material layer includes a metal lithium layer, a lithium alloy layer, or a combination of the two; wherein the lithium alloy layer includes an alloy of lithium and one or more of silicon, indium, silver, carbon, magnesium, aluminum, boron, tin, gallium, cobalt, gold, barium, bismuth, calcium, germanium, mercury, platinum, zinc, lead, antimony, cadmium, and cobalt; The thickness of the active material layer is 3 μm-300 μm; The thickness ratio of the control layer to the active material layer is (0.001-1):
1.
5. The anti-dendritic lithium metal negative electrode according to claim 1, characterized in that The lithium metal negative electrode also includes a current collector, which includes at least one of copper foil, aluminum foil, stainless steel foil, nickel foil, tin foil, carbon nanotube paper, carbon fiber paper, copper mesh, aluminum mesh, stainless steel mesh, nickel foam, and an organic fiber film with a metal plated surface.
6. A method for preparing the anti-dendritic lithium metal negative electrode according to any one of claims 1 to 5, characterized in that: The method comprises: (1) Plasma cleaning and drying of boron nitride nanotubes and solid electrolyte materials; (2) Weigh corresponding proportions of boron nitride nanotubes, polymer matrix and inorganic reinforcement material, mix them, refine the powder particles and mix them evenly; (3) Weighing a certain amount of solvent, adding lithium salt, thickener and hydrophilic additive according to corresponding mass fractions, mixing and stirring, and then adding the mixture of boron nitride nanotubes, polymer matrix and inorganic reinforcing material obtained in step (2), mixing and stirring to obtain a uniform and viscous slurry; (4) The slurry obtained in step (3) is disposed on the surface of the active material layer to form a uniform coating, and the coating is dried to obtain the anti-dendrite lithium metal negative electrode.
7. The method according to claim 6, characterized in that The gas used for plasma cleaning in step (1) includes one or a combination of two of hydrogen, oxygen, nitrogen, argon, and helium; The plasma cleaning time described in step (1) is 3-5 minutes; The drying and dehumidification temperature in step (1) is 60-100°C, and the drying time is 1-5h.
8. The method according to claim 6 or 7, characterized in that: The method for mixing the boron nitride nanotubes, the polymer matrix and the inorganic reinforcing material in step (2) includes ball milling, chemical precipitation, sol-gel and ultrasonic mixing, wherein the ball milling speed of the ball milling method is 100-600 rpm and the ball milling time is 3-6 hours; The solvent in step (3) includes any one of N-methylpyrrolidone, tetrahydrofuran, dimethyl ether, dichloromethane, ethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, diethylene glycol monomethyl ether, tetraethylene glycol dimethyl ether, dimethyl sulfate, polyether ketone, or a combination of at least two thereof; The mass ratio of the lithium salt, thickener, hydrophilic additive and solvent in step (3) is (1-5): (1-5): (1-5): (85-97); The mass ratio of the boron nitride nanotubes, polymer matrix, inorganic reinforcing material and solvent in step (3) is (0.5-2): (0.1-2): (0.1-1): (95-99.3); In step (3), lithium salt, thickener and hydrophilic additive are added and mixed at a speed of more than 1100 rpm for 1-20 hours; In step (3), boron nitride nanotubes are added, and the polymer matrix and the inorganic reinforcing material are mixed and stirred at a speed of more than 1200 rpm for a stirring time of 1-20 hours.
9. The method according to claim 6, characterized in that The method of disposing the slurry of step (3) on the active material layer in step (4) includes any one of coating, film transfer, spraying, spin coating, roller pressing, and immersion, or a combination of at least two of them.
10. A solid-state battery, characterized in that: The solid-state battery includes a positive electrode, a negative electrode and a solid electrolyte disposed between the positive electrode and the negative electrode; wherein the negative electrode is the anti-dendritic lithium metal negative electrode described in any one of claims 1-5, and the active material of the positive electrode is any one of layered oxides, polyanion active materials, lithium-rich oxides or spinel oxides, or a combination of at least two thereof; the solid-state battery includes a lithium-sulfur solid-state battery, a bipolar solid-state battery, a sulfide solid-state battery, a polymer solid-state battery, a halide solid-state battery, an oxide solid-state battery, and an organic-inorganic composite solid-state battery.
Citation Information
Patent Citations
Negative electrode for lithium metal battery and lithium metal battery comprising the same
CN107394115A
Method for protecting lithium metal negative electrode, lithium metal negative electrode and lithium battery
CN108365178A
Lithium battery slurry, lithium metal cathode composite layer and lithium metal cathode as well as preparation method and application thereof
CN110600740A
Flexible boron nitride nanotube inorganic diaphragm, preparation thereof and application of flexible boron nitride nanotube inorganic diaphragm in lithium secondary battery
CN114421093A
Lithium metal and solid electrolyte interface layer and preparation method
CN114824459A
Cited By
Sodium metal negative electrode material for constructing hybrid solid electrolyte interface layer based on gas-liquid mixed plasma one-step method as well as preparation method and application of sodium metal negative electrode material
CN120127111A
Solid electrolyte layer, and solid-state battery and electronic device comprising same
CN121123379A